Multi-spacecraft determination of wave characteristics near the proton gyrofrequency in high-altitude cusp - D. Sundkvist; D. Sundkvist; D. Sundkvist; A. Vaivads; M. André; J.-E. Wahlund; Y. Hobara; S. Joko; V. V. Krasnoselskikh; Y. V. Bogdanova; S. C. Buchert; N. Cornilleau-Wehrlin; et al. (Annales Geophysicae, 2005)
We present a detailed study of waves with frequencies near the proton gyrofrequency in the high-altitude cusp for northward IMF as observed by the Cluster spacecraft. Waves in this regime can be important for energization of ions and electrons and for energy transfer between different plasma populations. These waves are present in the entire cusp with the highest amplitudes being associated with localized regions of downward precipitating ions, most probably originating from the reconnection site at the magnetopause. The Poynting flux carried by these waves is downward/upward at frequencies below/above the proton gyrofrequency, which is consistent with the waves being generated near the local proton gyrofrequency in an extended region along the flux tube. We suggest that the waves can be generated by the precipitating ions that show shell-like distributions. There is no clear polarization of the perpendicular wave components with respect to the background magnetic field, while the waves are polarized in a parallel-perpendicular plane. The coherence length is of the order of one ion-gyroradius in the direction perpendicular to the ambient magnetic field and a few times larger or more in the parallel direction. The perpendicular phase velocity was found to be of the order of 100km/s, an order of magnitude lower than the local Alfvén speed. The perpendicular wavelength is of the order of a few proton gyroradius or less. Based on our multi-spacecraft observations we conclude that the waves cannot be ion-whistlers, while we suggest that the waves can belong to the kinetic Alfvén branch below the proton gyrofrequency fcp and be described as non-potential ion-cyclotron waves (electromagnetic ion-Bernstein waves) above. Linear wave growth calculations using kinetic code show considerable wave growth of non-potential ion cyclotron waves at wavelengths agreeing with observations. Inhomogeneities in the plasma on the order of the ion-gyroradius suggests that inhomogeneous (drift) or nonlinear effects or both of these should be taken into account.